Associations of attention distractibility with attention deficit and with variation in the KTN1 gene. (1st November 2020) - Tuvi, Iiris; Harro, Jaanus; Kiive, Evelyn; Vaht, Mariliis; Bachmann, Talis
Highlights: Prolonged reaction times to distractor and inattention scores were uncorrelated. Motor restlessness of adolescents decreases in adulthood. Coefficient of variability of reaction time was associated with gene KTN1 rs945270. Abstract: Attention distractibility in a low load visual search experiment with a rare irrelevant distractor could be an objective continuous measure in adulthood that correlates well with the symptoms of attention deficit throughout lifespan. This was studied using a birth cohort representative sample in a longitudinal study. The expected correlations were not found between the distractor cost measured in the experiment in adulthood and the inattention questionnaire scores from ages 15−33. However, the coefficient of variability for RT (CVRT) correlated negatively with self-reported motor restlessness (age 15) and attention deficit (age 25). We suggest that hyperactivity in childhood improved motor control at age 33. Associations with the gene KTN1 rs945270 (found to affect putamen size) were explored. CVRT, motor restlessness at age 15 and attention deficit scores at age 25 were especially low for male C-allele carriers. A possible association with the volume of putamen of individual participants is considered.